The Status and Role of Pictograms in the Communicative Space of Modern English - Makaruk, Laryssa (East European Journal of Psycholinguistics, 2015)
This article deals with pictograms which are used in the communicative space of modern English in place of phonemes, morphemes and lexemes. In the examples which are given, we see that in most cases morphemes and singular phonemes are replaced by graphical elements. With respect to the replacement of lexemes, it is mainly the verbs used in statements and questions which for which a substitution occurs. Paralinguistic units are contextually dependent and their semantics correlates with the verbal part through various types of relations. The most distinctive feature of modern multimodal discourse is the combination of signs belonging to the codes of two semiotic systems—verbal and non-verbal. Paralinguistic graphic means, which can be included in a text, modify its structure and add additional shades of meaning to it. The role and the status of pictograms have been defined. Pictograms are important textual elements in the creation of a text. Their distinctive features have been defined and their paradigmatic relations have been identified. In the process of analysing the peculiarities of pictograms, sociocultural factors have been taken into account. References Diringer, D. (2004). Alfavit [Alphabet]. Мoscow: URSS. Yermolenko, L. (2005). Piktohrafichni ta ideohrafichni znaky u suchasnii frantsuzkii movi [Pictographic and Ideographic Signs in Modern French]. Кyiv: Karpenko Publishers. Karpenko, Yu. ( 2006). Vstyp do Movoznavstva [Introductin to Linguistics]. Кyiv: Akademiia. Kotstsolino, M. (2009). Nievierbalnaia Kommunikatsyia. [Nonverbal Communication]. Kharkiv: Gumanitarnyi Tsentr. Kreidlin, G. and Krongauz, M. (2009). Semiotika, ili Azbuka Obshcheniia [Semiotics, Or Bases of Communication]. Мoscow: Flinta; Nauka. Yartseva, V. (ed.) (1990). Lingvisticheskii Entsyklopedicheskii Slovar. Мoscow: Sovetskaia Entsyklopediia. Makaruk, L. (2013). Linhvoprahmatyka piktohram ta ideohram v anhliiskomu masmediinomu dyskursi [Linguistic pragmatics of pictograms and ideograms in English discourse of mass media]. Ph.D. dissertation. Lviv: Ivan Franko National University of Lviv. Seriakova, I. (1999). K voprosu o funktsyiakh neverbalnogo znaka v kommunikativnom akte [On functions of nonverbal sign in communicative act]. Naukovyi Visnyk VNU. Series “Philology”, 3, 72–74. Soloshchuk, L. (2006). Verbalni i neverbalni komponenty komunikatsii v anhlomovnomu dyskursi [Verbal and Non-vebal Components of Communication in English Discourse]. Kharkiv: Konstanta. Utevskaia, P. (1985). Slov dragotsennyie klady. Rasskazy o pismennosti [Precious Words]. Мoscow: Detskaia Literatura. Abdullah, R. and Hubner, R. (2007). Pictograms, Icons @ Signs: A Guide to Information Graphics. Published by Thames @ Hudson Inc. Guerro, L. K. (1994). Nonverbal Communication. New York. Poyatos, F. (1997). Problems and challenges of nonverbal communication. Nonverbal Communication in Translation. Amsterdam/Philadelphia, 11–29. Sources Grand Canyon National Park. Your Complete Guide to the Parks. (2014). APN MEDIA, LLC. Graphic Design Junction (2015, March 5) Retrieved from http://graphicdesignjunction.com/2012/03/90-modern-pictograms-typeface-interface-designers/ Herts, Viktor. Singers’ Lives in Pictograms (2015, March 5) Retrieved from [http://www.ink-system.co.uk/articles/inspiration/singers-lives-in-pictograms.htm] Shutterstock (2015, March 5) Retrieved from http://www.shutterstock.com/pic223093918/stock-vector-teamwork-infographic-set-with-business-process-pictograms-and-worldmap-vector-illustration.html?src=ut9x5oqjqnad87OOxrRxAg-1-79